Community NY: Earth Science: The World We Live In: Samuel N. Namowitz and the Reimagining of Earth Science Education in New York State and the Nation. - Landa, Edward R. (New York History)
The article focuses on the significant role of New York in the development of Earth science education in the United States during the mid-twentieth century. It highlights the transition from a traditional physical geography curriculum to a more dynamic Earth Science program initiated in 1940, largely influenced by educators like Samuel N. Namowitz and Donald B. Stone. The article details the growth of Earth science enrollment in New York schools, the creation of a foundational textbook, and the challenges faced in establishing Earth science as a respected academic discipline. It also notes the lasting impact of these educational reforms on students and the broader field of geosciences.